2019
DOI: 10.1039/c9nr03593a
|View full text |Cite
|
Sign up to set email alerts
|

Mixed dysprosium-lanthanide nitride clusterfullerenes DyM2N@C80-Ihand Dy2MN@C80-Ih(M = Gd, Er, Tm, and Lu): synthesis, molecular structure, and quantum motion of the endohedral nitrogen atom

Abstract: The impact of the second metal on the synthesis and molecular structure of Dy–M nitride clusterfullerenes (M = Gd, Er, Tm, Lu) is evaluated systematically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 95 publications
5
31
0
Order By: Relevance
“…Noteworthily, an interesting report from Olmstead and co‐workers detailed a systematic study analyzing the pyramidalization of the M 3 N (M=Gd, Tb, Dy, Ho, Er, Tm, Lu, and Sc) units inside the I h (7)‐C 80 cage, revealing that the M 3 N unit becomes pyramidalized to some extent when the sum of the Shannon–Prewitt crystal radii of the three metal ions involved exceeds 3.05 Å, and this result is applicable to endohedrals in which all three metal ions are identical or totally different . Consistently, Popov and colleagues confirmed that in the mixed‐metal NCFs, DyM 2 N@ I h (7)‐C 80 (M=Er, Gd), the N atom in DyEr 2 N is located in the plane of DyEr 2 (Figure c), whereas the DyGd 2 N cluster is pyramidal with the sum of the three M‐N‐M angles of 345.9° (Figure d), as the Gd atom is too large to maintain the planarity of the cluster in C 80 .…”
Section: Nitride Clusterfullerenesmentioning
confidence: 95%
See 1 more Smart Citation
“…Noteworthily, an interesting report from Olmstead and co‐workers detailed a systematic study analyzing the pyramidalization of the M 3 N (M=Gd, Tb, Dy, Ho, Er, Tm, Lu, and Sc) units inside the I h (7)‐C 80 cage, revealing that the M 3 N unit becomes pyramidalized to some extent when the sum of the Shannon–Prewitt crystal radii of the three metal ions involved exceeds 3.05 Å, and this result is applicable to endohedrals in which all three metal ions are identical or totally different . Consistently, Popov and colleagues confirmed that in the mixed‐metal NCFs, DyM 2 N@ I h (7)‐C 80 (M=Er, Gd), the N atom in DyEr 2 N is located in the plane of DyEr 2 (Figure c), whereas the DyGd 2 N cluster is pyramidal with the sum of the three M‐N‐M angles of 345.9° (Figure d), as the Gd atom is too large to maintain the planarity of the cluster in C 80 .…”
Section: Nitride Clusterfullerenesmentioning
confidence: 95%
“… Molecular structures of (a) Ho 3 N@ C 2 (22010)‐C 78 , (b) Tb 3 N@ C 2 (22010)‐C 78 , (c) DyEr 2 N@ I h (7)‐C 80 , and (d) DyGd 2 N@ I h (7)‐C 80 . Fused pentagon pairs are highlighted in red.…”
Section: Nitride Clusterfullerenesmentioning
confidence: 99%
“…Dy 2 GdN@C 80 endofullerenes were produced by arcdischarge synthesis using the corresponding metals [15]. The subsequent separation by high-pressure liquid chromatography resulted in a sample of 95% purity with 5% Dy 3 N@C 80 contamination as inferred from time-of-flight mass spectrometry [25].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…First magnetic studies were performed on Gd@C 82 [12], and it took 17 more years until SMM behavior in endohedral fullerenes was found with DySc 2 N@C 80 [13]. In the following many different C 80 mixed dysprosium-lanthanide nitride clusters have been synthesized and magnetically characterized [14][15][16]. As in other radical bridged lanthanide complexes [17] dysprosium ion pairs appear to form excellent SMMs [18].…”
Section: Introductionmentioning
confidence: 99%
“…For this, we chose lutetium as a diamagnetic lanthanide, the ionic radius ( R 3+ =0.86 Å) of which is noticeably larger than that of scandium ( R 3+ =0.75 Å). Yet, as we reported recently, DyLu 2 N@C 80 ‐ I h and Dy 2 LuN@C 80 ‐ I h can still be synthesized, albeit in lower yields than the dysprosium‐scandium analogues . The larger size of Lu 3+ leads to changes in the internal structure of the trimetallic nitride cluster, and in particular results in shorter Dy−N bonds than in the dysprosium‐scandium NCFs.…”
Section: Introductionmentioning
confidence: 92%